2006
DOI: 10.1152/ajplung.00027.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic exposure to ozone alters distal airway development in infant rhesus monkeys

Abstract: Inner city children exposed to high levels of ozone suffer from an increased prevalence of respiratory diseases. Lung development in children is a long-term process, and there is a significant period of time during development when children growing up in urban areas are exposed to oxidant air pollution. This study was designed to test whether repeating cycles of injury and repair caused by episodes of ozone exposure lead to chronic airway disease and decreased lung function by altering normal lung maturation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 43 publications
5
74
0
Order By: Relevance
“…Additional subchronic and chronic ozone exposure studies (500 ppb) in rhesus monkeys have demonstrated structural changes in the distal and proximal airways (Fanucchi et al, 2006;Carey et al, 2011) and allergy-like patterns of response (increased globlet cells and eosinophils) to allergen and ozone co-challenges (Kajekar et al, 2007;Miller et al, 2009;van Winkle et al, 2010;Plopper et al, 2007). These studies would therefore seem to support the epidemiological observations that reported impaired lung growth (peak flow: Gauderman et al, 2002;FVC and FEV1: Rojas-Martinez et al, 2007) and a worsening of asthma symptoms in children with high ozone exposures (asthma incidence: McConnell et al, 2002;Islam et al, 2009;asthma medication usage: Millstein et al, 2004).…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%
“…Additional subchronic and chronic ozone exposure studies (500 ppb) in rhesus monkeys have demonstrated structural changes in the distal and proximal airways (Fanucchi et al, 2006;Carey et al, 2011) and allergy-like patterns of response (increased globlet cells and eosinophils) to allergen and ozone co-challenges (Kajekar et al, 2007;Miller et al, 2009;van Winkle et al, 2010;Plopper et al, 2007). These studies would therefore seem to support the epidemiological observations that reported impaired lung growth (peak flow: Gauderman et al, 2002;FVC and FEV1: Rojas-Martinez et al, 2007) and a worsening of asthma symptoms in children with high ozone exposures (asthma incidence: McConnell et al, 2002;Islam et al, 2009;asthma medication usage: Millstein et al, 2004).…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%
“…Although the nonrespiratory airways of rats and humans do not form additional branches postnatally, they exhibit proportional increases in length and diameter, the diameters of terminal bronchioles at 18 years of age in humans being about 2-fold those at 2 years of age and more than 5-fold those of a neonate (30,31). Whether early viral airway injury alters normal growth of conducting airways is not known, but a study of intermittent exposure of infant monkeys to ozone, a noninfectious airway insult, found that terminal bronchioles were significantly narrower and shorter in the ozone group (32).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two important nonhuman primate models of respiratory syncytial virus (RSV) and bronchial asthma and RSV have been developed in the baboon and Rhesus monkey, respectively. These models are again important in reflecting physiological, immunological, and morphological similarities to human neonatal/pediatric diseases (27,58). Additionally, both are known to significantly impact lung function in affected children who survive preterm birth.…”
Section: Advantages Of the Baboon And Nonhuman Primate Modelsmentioning
confidence: 99%